2003
DOI: 10.1074/jbc.m301358200
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Transport by the Human Breast Cancer Resistance Protein (ABCG2) Expressed in Lactococcus lactis

Abstract: The emergence of multidrug resistant cancer cells is a serious problem in the chemotherapeutic treatment of human tumors. In mammals, multidrug resistance based on the active extrusion of cytotoxic drugs from the cell is mediated by several members of the ATP-binding cassette (ABC) 1 superfamily. These include the multidrug resistance P-glycoprotein MDR1 (also termed ABCB1) and the protein MRP1 (multidrug resistance-associated protein 1, also termed ABCC1) (1). The breast cancer resistance protein (BCRP, also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
95
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 32 publications
6
95
2
1
Order By: Relevance
“…They also demonstrated that the mean BCRP protein level in the placenta was lower in homozygotes for the A421 allele than in those for the C421 allele and that heterozygotes had an intermediate level. 26 Although the molecular mechanism for the relationship between BCRP and carcinogenesis remains to be resolved, BCRP transports a wide variety of substances other than anticancer drugs, including fluorescent dyes, 27 sterols, 28 phytoestrogens, 29 chlorophyll derivatives 30 and folate. 31 Pheophorbide a, a chlorophyll derivative, was shown to have antimutagenic activity and to inhibit tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that the mean BCRP protein level in the placenta was lower in homozygotes for the A421 allele than in those for the C421 allele and that heterozygotes had an intermediate level. 26 Although the molecular mechanism for the relationship between BCRP and carcinogenesis remains to be resolved, BCRP transports a wide variety of substances other than anticancer drugs, including fluorescent dyes, 27 sterols, 28 phytoestrogens, 29 chlorophyll derivatives 30 and folate. 31 Pheophorbide a, a chlorophyll derivative, was shown to have antimutagenic activity and to inhibit tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to androgen, a large set of BCRP substrates has been identified including chemotherapeutic agents, fluorescent dyes, as well as chemical toxicants (16). BCRP overexpression has been detected in a variety of mitoxantrone or other chemotherapeutic agents selected cell lines (17,18). The molecular mechanism of BCRP in drug efflux has been well studied in breast cancer cells.…”
mentioning
confidence: 99%
“…Although a physiological function of ABCG2 remains to be established, the tissue distribution suggests a role of the protein in the protection against xenobiotics. Lately, ABCG2 has been found in relation to stem cells (15,16) and sterol transport (17).…”
mentioning
confidence: 99%